Impact of proton pump inhibitor treatment on gastrointestinal bleeding associated with non-steroidal anti-inflammatory drug use among post-myocardial infarction patients taking antithrombotics: nationwide study. (19th October 2015) - Schjerning Olsen, Anne-Marie; Lindhardsen, Jesper; Gislason, Gunnar H; McGettigan, Patricia; Hlatky, Mark A; Fosbøl, Emil; Køber, Lars; Torp-Pedersen, Christian; Lamberts, Morten
Abstract : Study question What is the effect of proton pump inhibitors (PPIs) on the risk of gastrointestinal bleeding in post-myocardial infarction patients taking antithrombotics and treated with non-steroidal anti-inflammatory drugs (NSAIDs)? Methods This was a nationwide cohort study based on linked administrative registry data from all hospitals in Denmark between 1997 and 2011. The study included patients aged 30 years and over admitted with a first myocardial infarction who survived at least 30 days after discharge. The association between PPIs and risk of gastrointestinal bleeding according to NSAID plus antithrombotic therapy was estimated using adjusted time dependent Cox regression models. Study answer and limitations The use of PPIs was independently associated with decreased risk of gastrointestinal bleeding in post-myocardial infarction patients taking antithrombotics and treated with NSAIDs. Of 82 955 post-myocardial infarction patients (mean age 67.4 years, 64% (n=53 070) men), all of whom were taking single or dual antithrombotic therapy, 42.5% (n=35 233) filled at least one prescription for NSAIDs and 45.5% (n=37 771) received PPIs. Over a mean follow-up of 5.1 years, 3229 gastrointestinal bleeds occurred. The crude incidence rates of bleeding (events/100 person years) on NSAID plus antithrombotic therapy were 1.8 for patients taking PPIs and 2.1 for those not taking PPIs. The adjusted risk of bleeding was lower with PPI use (hazard ratio 0.72, 95% confidence interval 0.54 to 0.95) regardless of antithrombotic treatment regimen, type of NSAID, and type of PPI used. The main limitation of the study is its observational non-randomised design. The results suggest that PPI treatment probably has a beneficial effect regardless of underlying gastrointestinal risk and that when NSAIDs cannot be avoided in post-myocardial infarction patients, physicians might prescribe a PPI as well. The study does not clarify whether PPIs might be safely omitted in specific subgroups of patients with a low risk of gastrointestinal bleeding. What this study adds In post-myocardial infarction patients, bleeding complications have been associated with both antithrombotic and NSAID treatment. Concurrent use of PPIs was independently associated with a decreased risk of gastrointestinal bleeding in post-myocardial infarction patients taking antithrombotics and NSAID, regardless of antithrombotic treatment regimen, type of NSAID, and type of PPI used. Funding, competing interests, data sharing AMSO has received a grant from the Danish Council of Independent Research (grant 12-132760). GHG is supported by an unrestricted research scholarship from the Novo Nordisk Foundation.